Robot-assisted complete excision of choledochal cyst type I, hepaticojejunostomy and extracorporeal Roux-en-y anastomosis: a case report and review literature - Suksamanapun Nutnicha; Trakarnsanga Atthaphorn; Akaraviputh Thawatchai (World Journal of Surgical Oncology, 2010)
Abstract For Choledochal cyst type I, complete excision of cyst with Roux-en-Y hepaticojejunostomy anastomosis is the treatment of choice. It has been performed laparoscopically with the advancement of laparoscopic skill. Recently, a telemanipulative robotic surgical system was introduced, providing laparoscopic instruments with wrist-arm technology and 3-dimensional visualization of the operative field. We present a case of robot-assisted total excision of a choledochal cyst type I and biliary reconstruction in a 14-year-old girl. No intraoperative complications or technical problems were encountered. An intraabdominal collection occurred and was successfully treated with continuous percutaneous drainage. At one-year follow-up, she is doing well without evidence of recurrent cholangitis.